Relações incestuosas: poder, violência sexual, moral e "artimanhas" da justiça. Uberlândia, 1940-1970 - Bacci, Cynara Marques Hayeck (2011)
The purpose of this paper is analyze crime-processes related to cases of sexual violence caused by fathers against daughters with ages between zero and seventeen years old at the decades of 1940, 1950, 1960 and 1970, in the city of Uberlândia at the state of Minas Gerais. Were used registries presented on the records to examine the relationship between imaginary of fear, construction and deconstruction of the notion and concept of what violence is, speech and juridical actions, silence and obscurity involving incest, power relations that exist in these practices, among others. Studies was made about the existence of a moralist and conservative speech that seem to intend on reversing the roles of each individual involved in such crimes, in other words, to transform victims into defendants and accused into victims. In this context, was possible to discuss the role of forensic medicine in justice s performance before a sexual violence crime. Afterwards, the text brings an argumentation about a specific juridical record, which makes us think about how the appropriation of moral values that exists on our society was made by the juridical speech. And so, we can understand a little of how the legal processes works, how the juridical speech is created, and how the victims are in a certain way silenced.